PENGEMBANGAN EKOWISATA DAN PENGARUHNYA PADA PEREKONOMIAN DAERAH DI KABUPATEN WAKATOBI, PROVINSI SULAWESI TENGGARA - , Wa Ode Kanufia Diki, Dr. M. Baiquni, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis is results of research done in Wakatobi district to identify tourism in ecotourism development with relation of its effect on local economy. Tourism management dominated by coastal tourism object and undersea panorama included four primary islands in Wakatobi, separated into tourism areas: Wangi-Wangi Island and islands around as Tourism area I